2024
DOI: 10.1038/s41467-024-46386-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 7-dehydrocholesterol reductase prevents hepatic ferroptosis under an active state of sterol synthesis

Naoya Yamada,
Tadayoshi Karasawa,
Junya Ito
et al.

Abstract: Recent evidence indicates ferroptosis is implicated in the pathophysiology of various liver diseases; however, the organ-specific regulation mechanism is poorly understood. Here, we demonstrate 7-dehydrocholesterol reductase (DHCR7), the terminal enzyme of cholesterol biosynthesis, as a regulator of ferroptosis in hepatocytes. Genetic and pharmacological inhibition (with AY9944) of DHCR7 suppress ferroptosis in human hepatocellular carcinoma Huh-7 cells. DHCR7 inhibition increases its substrate, 7-dehydrochole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Since GPX4 belongs to the selenoprotein family, which is characterized by proteins carrying at least one selenocysteine (Sec) usually in their active site, this residue is critical for enabling full GPX4 enzymatic activity and protection from peroxide-inducible, irreversible overoxidation and enzyme inactivation 12 . In addition to the GSH/GPX4 axis, a series of genetic screens have unveiled alternative ferroptosis surveillance systems, such as the NAD(P)H/ferroptosis suppressor protein-1 (FSP1)/ubiquinone or vitamin K system 1315 , di-/tetrahydrobiopterin/GTP cyclohydrolase 1 (GCH1)/dihydrofolate reductase (DHFR) system 16,17 and 7-dihydrocholesterol reductase (DHCR7) 1820 , that can act as backup systems for GPX4 at least in certain cellular contexts. Unlike GPX4, these systems protect against the lipid peroxidation chain reaction by reducing phospholipid peroxyl radicals to phospholipid hydroperoxides that require additional steps for their decomposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since GPX4 belongs to the selenoprotein family, which is characterized by proteins carrying at least one selenocysteine (Sec) usually in their active site, this residue is critical for enabling full GPX4 enzymatic activity and protection from peroxide-inducible, irreversible overoxidation and enzyme inactivation 12 . In addition to the GSH/GPX4 axis, a series of genetic screens have unveiled alternative ferroptosis surveillance systems, such as the NAD(P)H/ferroptosis suppressor protein-1 (FSP1)/ubiquinone or vitamin K system 1315 , di-/tetrahydrobiopterin/GTP cyclohydrolase 1 (GCH1)/dihydrofolate reductase (DHFR) system 16,17 and 7-dihydrocholesterol reductase (DHCR7) 1820 , that can act as backup systems for GPX4 at least in certain cellular contexts. Unlike GPX4, these systems protect against the lipid peroxidation chain reaction by reducing phospholipid peroxyl radicals to phospholipid hydroperoxides that require additional steps for their decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work suggested that genetic perturbation of PRDX6 renders cancer cells more vulnerable to ferroptosis 2527 . In addition, PRDX6 has been repeatedly identified in genetic screens or gene cluster analyses aimed at identifying genes impinging on ferroptosis regulation 17,28 . However, the mechanisms by which PRDX6 modulate ferroptosis susceptibility or its impact on PLOOH reduction remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%